Palay ; Earthquake - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles palay price hike and interviews with Prof. Tamesis about earthquake, structure Engr. Octavio Calalo and othe engineers about Philippine building construction.
Palay (12 min.) -- Earthquake (17 min.)
VHS.
Keywords: Grain -- Prices -- Philippines; Building laws -- Philippines; Buildings -- Earthquakes effects; Earthquakes resistant design; Palay -- Marketing -- Philippines